Design and experiment of a bionic vibratory subsoiler for banana fields in southern China - Xirui, Zhang; Chao, Wang; Zhishui, Chen; Zhiwei, Zeng (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Subsoiling is essential in the tillage of banana planting, as banana plants have a fairly sturdy pseudostem and wide row spacing while soil tends to be compacted. In this study, a bionic vibrating subsoiler for banana fields was developed, verified, and evaluated. The vibrator was designed based on crank-rocker mechanism while the bionics design was used for subsoiler development. The forces on the susboiler were analyzed to verify the strength of the subsoiler tine. To test the performance of the subsoiler, field tests were conducted to measure the draft force and fuel consumption. There was approximately 14% reduction in the draft force and 22% increase in the fuel consumption in vibrating mode compared with that in non-vibrating mode. In conclusion, the study results could be applied in China’s tropical agricultural regions. Keywords: vibratory subsoiler, tillage, simulation, bionics, banana field DOI: 10.3965/j.ijabe.20160906.1923 Citation: Zhang X R, Wang C, Chen Z H, Zeng Z W. Design and experiment of a bionic vibratory subsoiler for banana fields in southern China. Int J Agric & Biol Eng, 2016; 9(6): 75－83.